Implementasi Peraturan Pemerintah Nomor 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil di Pemerintah Kabupaten Kutai Barat - Desy Ratnasari; Husni Thamrin; Sisilia (LPPM STIH Awang Long, 2022)
To realize civil servants who are reliable, professional and moral as government administrators who apply the principles of good governance, civil servants as elements of the state apparatus are required to be loyal and obedient to Pancasila, the 1945 Constitution of the Republic of Indonesia, The Unitary State of the Republic of Indonesia and the government as well as being disciplined, honest, fair, transparent and accountable in carrying out their duties. The aim is to further ensure order and smooth implementation of the main duties and functions of civil servants, encourage increased performance and change in attitudes and behavior of civil servants, increase civil servant discipline, increase civil servant responsibilities, accelerate the process of change towards increasing professionalism in work. The author uses the library research method or literature review. This library research research is to conduct research from library books, magazines, journals and articles and sources from the internet that are relevant to the issues discussed. The following is a study based on Government Regulation Number 94 of 2021 Concerning Civil Service Discipline.